A study on intertextuality of Chinese traditional pentatonic rhythm and space narrative of Suzhou gardens - Yang Liu; Bo Shu; Yang Chen; Hao Zhang; Hao Zheng; RuiZhi Zhang (Journal of Asian Architecture and Building Engineering)
The traditional Chinese pentatonic rhythm and Suzhou Gardens are adhering to the traditional Chinese aesthetic concept, focusing on artistic conception, atmosphere, narrative and emotional expression. Taking the four major Gardens in Suzhou and the Chinese-style song “Sheng Sheng Man” as an example, this study attempts to analyze the intertextuality of emotional narrative between traditional Chinese pentatonic rhythm and Suzhou Gardens space by means of quantitative and qualitative combination of specific technical means, and to explore the internal correlation mechanism between Chinese Suzhou Gardens and traditional Chinese pentatonic rhythm through the study of intertextuality. Including similarity and fluency in narrative structure; Euphoric and soothing characteristics of emotional expression. It provides support for exploring the underlying logic of Chinese traditional cultural expression and revealing the deeper connotation of Chinese traditional culture.It also provides a new perspective for understanding the cultural connotations of Chinese gardens.